ANALYSIS OF UI & UX DRIVER MOBILE SYSTEM USING HEURISTIC EVALUATION METHOD - Fikry Aldi Afandi; Supriyadi Supriyadi (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
In the 4.0 era, user interface and user experience are considered key factors in the development of digital products, especially mobile applications. The progress and performance of the application is facilitated by the user interface and user experience applied to the application. Apart from presenting an attractive application appearance, implementing a user interface and user experience for an application makes using the application easier. DMS Mobile is an information system application used by drivers which is an information system application that is easy to use for drivers to run their work activities smoothly. Testing the user interface and user experience with the user experience, in this case the driver, can be a reference for assessing the DMS Mobile application. In this user aspect approach, the researchers carried out an evaluation through a questionnaire which would be answered by respondents from PT drivers. Seino Indomobil Logistic with simple random sampling. From the research results that need to be improved, namely the criteria for User control and freedom and Flexibility and efficiency of use which still have minimal percentages. The results obtained from calculations using the heuristic method are, the age criteria of respondents aged 18 - 25 years have a percentage of 9.2% of the total respondent data, while the second is that the age of respondents is 26 - 33 years with 46.1%, and the age criteria of respondents lastly at 34 – 40 years with 44.7%.To improve it, the author used several steps, namely improving the user interface (UI), and user testing to improve the interface so that it is easier to use.